Statistical modeling to characterize relationships between knee anatomy and kinematics. Issue 11 (23rd June 2015) - Smoger, Lowell M.; Fitzpatrick, Clare K.; Clary, Chadd W.; Cyr, Adam J.; Maletsky, Lorin P.; Rullkoetter, Paul J.; Laz, Peter J.
ABSTRACT: The mechanics of the knee are complex and dependent on the shape of the articular surfaces and their relative alignment. Insight into how anatomy relates to kinematics can establish biomechanical norms, support the diagnosis and treatment of various pathologies (e.g., patellar maltracking) and inform implant design. Prior studies have used correlations to identify anatomical measures related to specific motions. The objective of this study was to describe relationships between knee anatomy and tibiofemoral (TF) and patellofemoral (PF) kinematics using a statistical shape and function modeling approach. A principal component (PC) analysis was performed on a 20‐specimen dataset consisting of shape of the bone and cartilage for the femur, tibia and patella derived from imaging and six‐degree‐of‐freedom TF and PF kinematics from cadaveric testing during a simulated squat. The PC modes characterized links between anatomy and kinematics; the first mode captured scaling and shape changes in the condylar radii and their influence on TF anterior–posterior translation, internal‐external rotation, and the location of the femoral lowest point. Subsequent modes described relations in patella shape and alta/baja alignment impacting PF kinematics. The complex interactions described with the data‐driven statistical approach provide insight into knee mechanics that is useful clinically and in implant design. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1620–1630, 2015.